2020
DOI: 10.1007/s12243-020-00799-8
|View full text |Cite
|
Sign up to set email alerts
|

Survey on physical layer security for 5G wireless networks

Abstract: Physical layer security is a promising approach that can benefit traditional encryption methods. The idea of physical layer security is to take advantage of the propagation medium's features and impairments to ensure secure communication in the physical layer. This work introduces a comprehensive review of the main information-theoretic metrics used to measure the secrecy performance in physical layer security. Furthermore, a theoretical framework related to the most commonly used physical layer security techn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 155 publications
(134 reference statements)
0
33
0
1
Order By: Relevance
“…Finally, we provide a quick explanation of the functions implemented in Algorithm 1. The PSO function returns the following results: (1) fobest: minimum value of the objective function, i.e., , in (12); (2) xgbest: optimal values of the fading parameters (e.g, µ, κ, m k , γ for the κ-µ shadowed model) of the the theoretical CDF that minimize (12). It is worth pointing out that the number of optimal values returned by the PSO algorithm depends on the fading channel model.…”
Section: Optimization Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, we provide a quick explanation of the functions implemented in Algorithm 1. The PSO function returns the following results: (1) fobest: minimum value of the objective function, i.e., , in (12); (2) xgbest: optimal values of the fading parameters (e.g, µ, κ, m k , γ for the κ-µ shadowed model) of the the theoretical CDF that minimize (12). It is worth pointing out that the number of optimal values returned by the PSO algorithm depends on the fading channel model.…”
Section: Optimization Proceduresmentioning
confidence: 99%
“…The increasing demands for new wireless applications/services and the rapid growth of connected intelligent "things" (also known as the internet of things (IoT) [1]) will saturate the capacity of current mobile communication systems in the coming years. Building on this background, network designers and researchers search for novel emerging technologies to ensure ultra-high data rates, energy efficiency, ultra-wide radio coverage, and connectivity, as well as ultra-low latencies and high reliability [2]. In this context, the fifth generation of wireless networks (5G) emerges as a solution to satisfy these strict requirements through intelligent and environmentally friendly technologies [3].…”
Section: Introductionmentioning
confidence: 99%
“…Analysis is complicated by the non-Gaussian nature of No methods currently exist for estimating upper bounds of the information-theoretic secret-key rate in (1). A dual analysis involves evaluation of the practical OFDM data rate.…”
Section: B Secret Key Transmission Ratesmentioning
confidence: 99%
“…Motivated by the need to achieve privacy at low latency, we propose using a technology known as Physical Layer Security (PLS). Physical Layer Security protects communication against eavesdroppers by tapping into the inherent randomness in the wireless medium between two communicating parties [1]. Furthermore, privacy algorithms integrate with the modulation at Layer 1 of the Open Systems Interconnect (OSI) stack such that the waveform leaving the antenna is private.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, researchers like Li et al [5] have shown in that spoofing attack is possible in 5G due to vulnerabilities in the Physical Layer. Sánchez et al [6] have highlighted the security issues related to the 5G wireless network. We can arrive at a hypothesis that there are still many vulnerabilities in the 5G network.…”
Section: *Author For Correspondencementioning
confidence: 99%